2020
DOI: 10.1057/s41599-020-00649-x
|View full text |Cite
|
Sign up to set email alerts
|

Human–dog relationships during the COVID-19 pandemic: booming dog adoption during social isolation

Abstract: The recent COVID-19 pandemic led to uncertainty and severe health and economic concerns. Previous studies indicated that owning a companion animal, such as a dog or a cat, has benefits for good mental health. Interactions with animals may help with depression and anxiety, particularly under stress-prone conditions. Human–animal interactions may even improve peer-to-peer social relationships, as well as enhance feelings of respect, trust, and empathy between people. Interestingly, it has also been shown that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 48 publications
3
84
1
1
Order By: Relevance
“…This study was approved by the University of Liverpool Veterinary Research Ethics Committee (VREC957) and was distributed via social media, including Facebook and Twitter. Many people acquired new pets during lockdown (e.g., "pandemic puppies" or rescue adoption [27]); however, our study recruited only those who had their dog both before and during this time, so that changes could be assessed. Dog owners also had to live in the UK and be over 18 years of age to be eligible to participate.…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…This study was approved by the University of Liverpool Veterinary Research Ethics Committee (VREC957) and was distributed via social media, including Facebook and Twitter. Many people acquired new pets during lockdown (e.g., "pandemic puppies" or rescue adoption [27]); however, our study recruited only those who had their dog both before and during this time, so that changes could be assessed. Dog owners also had to live in the UK and be over 18 years of age to be eligible to participate.…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…Our study revealed that the web interest on adoption of cats and dogs increased during the early phase of the COVID-19 pandemic (35) and appeared to be sustainable for that of cats but not dogs. The affection between human and companion animals is well-recognized as an effective way to minimize stress during an uncertain period and help alleviating depression and anxiety upon social isolation (7,26,36). In face of disasters, the majority of pet owners are not willing to surrender their companion animals (37).…”
Section: Discussionmentioning
confidence: 99%
“…In face of disasters, the majority of pet owners are not willing to surrender their companion animals (37). Although there are reports of increasing pet abandonment during the pandemic, it appeared that the increased rates of adoption have canceled out the number of surrendered pets (7,10). Other than adoption, studies have also reported an increase in the number of foster families for the temporary stay of animals pending for adoption and a shorter length of stay for animals in shelters (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential welfare benefit pertains to a decrease in euthanasia of sheltersurrendered companion animals, concomitant with an increase in adoption rates during the pandemic [22][23][24] as people facing mandated social isolation for unknown periods of time sought nonhuman company. China also reclassified dogs as "pets," rather than as livestock, in a move towards reducing consumption of these animals [25].…”
Section: Potential Animal Welfare Impacts Of the Covid-19 Pandemicmentioning
confidence: 99%